Relationship between Education Level, Social Relationships, and Sleep Quality towards the Quality of Life of Pre-Elderly People in Laweyan District - Anantasya, Arum Widya; Ichsan, Burhannudin (Jurnal Vocational Nursing Sciences (VNUS), 2025)
Pre-elderly individuals (aged 45-59 years) face risks of functional decline, impacting their quality of life. Factors such as education level, social relationships, and sleep quality are known to influence quality of life in this demographic. An analytical observational study with a cross-sectional design was conducted on 75 respondents selected through purposive sampling. Data were collected using WHOQOL-BREF, Social Provisions Scale, and Pittsburgh Sleep Quality Index questionnaires. Bivariate analysis revealed significant correlations between education level (r=0.386; p=0.001), social relationships (r=0.681; p=0.000), and sleep quality (r=-0.555; p=0.000) with quality of life. Collectively, these factors explained 55.7% of the variation in quality of life (R²=0.557). Education level, social relationships, and sleep quality significantly influence the quality of life of pre-elderly individuals, with sleep quality as the most dominant factor. These findings suggest targeted interventions may improve pre-elderly well-being.